The relationship between age and parity and the occurrence anemia in pregnant women at Umbulharjo II Primary Health Center in 2018 - Fijri Rachmawati; Dhesi Ari Astuti (Universitas 'Aisyiyah Yogyakarta, 2020)
The maternal mortality rate in Indonesia is still high at 359 of 100,000 live births, the cause of death on mothers in Indonesia is 30,3% of bleeding, 27,1% of eclampsia, 7,3% of infection, 5% of prolonged labor, 5% of abortion and 25,3% of others. Bleeding is still ranked first as a contributor to the high maternal mortality rate and anemia is one of the causes of bleeding. This study aimed to determine the relationship between age and parity and the anemia in pregnant women in Umbulharjo II Primary Health Center. The design of this study was analytical with a cross sectional approach which analyzed the anemia based on secondary data at Umbulharjo II Public Health Center in 2017. Data analysis used chi-square and Regression Logistic using SPSS 22 for Windows with p-value 0.05 and 95% of CI. The result of data analysis obtained p-value of age (0,021 0,05), (OR=2,357, 95% of CI, (1,219-4,557) and p value of parity (0,042 0,05), (OR =2,204, 95% of CI, (1,123-4,325). In conclusion, age had a significant relationship with the occurrence anemia in pregnancy and parity had a significant relationship with the occurrence anemia in pregnancy.